A Novel LINS1 Truncating Mutation in Autosomal Recessive Nonsyndromic Intellectual Disability - Muthusamy, Babylakshmi; Bellad, Anikha; Prasad, Pramada; Bandari, Aravind K.; Bhuvanalakshmi, G.; Kiragasur, R. M.; Girimaji, Satish Chandra; Pandey, Akhilesh (Frontiers in Psychiatry, 2020)
The large majority of cases with intellectual disability are syndromic (i.e. occur with other well-defined clinical phenotypes) and have been studied extensively. Autosomal recessive non-syndromic intellectual disability is a group of genetically heterogeneous disorders for which a number of potentially causative genes have been identified although the molecular basis of most of them remains unexplored. Here, we report the clinical characteristics and genetic findings of a family with two male siblings affected with autosomal recessive non-syndromic intellectual disability. Whole exome sequencing was carried out on two affected male siblings and unaffected parents. A potentially pathogenic variant identified in this study was confirmed by Sanger sequencing to be inherited in an autosomal recessive fashion. We identified a novel nonsense mutation (p.Gln368Ter) in the LINS1 gene which leads to loss of 389 amino acids in the C-terminus of the encoded protein. The truncation mutation causes a complete loss of LINES_C domain along with loss of three known phosphorylation sites and a known ubiquitylation site in addition to other evolutionarily conserved regions of LINS1. LINS1 has been reported to cause MRT27 (mental retardation, autosomal recessive 27), a rare autosomal recessive non-syndromic intellectual disability, with limited characterization of the phenotype. Identification of a potentially pathogenic truncating mutation in LINS1 in two profoundly intellectually impaired patients also confirms its role in cognition.